4G LTE NETWORK WALK TEST ANALYSIS USING ANDROID APPLICATION G-NET TRACK ON SWCU FTI BUILDING - Yosefhin Rayaruna Yungka; Dian Chandra Widiyanto (Informatika, Universitas Jenderal Soedirman, 2023)
The poor performance of a cellular network can hinder student academic activities such as the difficulty of accessing online materials. Therefore, this research aims to obtain data on the quality of the 4G LTE cellular network in the SWCU FTI building area so that the data can be used as a reference for improving network quality. The parameters used for analysis are RSRP (Reference Signal Received Power), RSRQ (Reference Signal Received Quality) and SINR (Signal Interference to Noise Ratio) parameters. The results of measurements in 21 data collection points show that the RSRP parameter shows that the overall average of Telkomsel operators is -111.05 dBm and Indosat operators is -114.48 dBm and based on KPI standards, it is categorized as very poor signal quality. For the RSRQ parameter, the average overall measurement results for Telkomsel operators is -16.25 dB and Indosat operators are -19.57 dB and based on KPI standards, it is categorized as poor signal quality. For SINR parameters, the overall average of Telkomsel operators is -7.5 dB and Indosat operators is -7.8 dB and based on KPI standards, it is categorized as poor signal quality.